MAIN DIRECTIONS AND WAYS TO CREATE SEZ IN UZBEKISTAN - Shonazarova Dilrabo Alisher qizi (Scholar Express Journals, 2022)
The article discusses the role of free economic zones in the development of an innovative economy, the conditions created in Uzbekistan to improve the activities of the free economic zones. It also clarified the priority directions of the created zones, the benefits granted and the conditions for doing business in them. Problems and tasks still remaining and requiring solution are given
Keywords: Strategy; tourism; high technology; technology